An algorithm to modify consistent initialization of differential-algebraic equations obtained by pantelides algorithm using minimally singular subsets - Keisuke Shimako; Masanobu Koga (SICE Journal of Control, Measurement, and System Integration, 2021)
In this paper, an algorithm for index reduction of differential algebraic equations (DAE) is proposed. Pantelides algorithm has already been proposed as an algorithm for this purpose. This conventional algorithm has succeeded in reducing the calculation time required for index reduction. However, there exist some DAE systems whose index cannot be reduced correctly with the conventional algorithm because it uses sufficient condition to reduce the index. We propose an algorithm to modify the solution obtained by Pantelides algorithm to deal with a wider class of DAE systems. The proposed algorithm deals with DAE systems by using the necessary and sufficient condition to reduce the index systematically that cannot be reduced by the conventional algorithm. We implemented the proposed algorithm as the functions on Maxima and evaluated the algorithm by using some examples.